Network Pharmacology Analysis of Cananga odorata as a Treatment for Anxiety Disorders - Maretha, Tri Luthfiana; Jamil, Ahmad Shobrun; Rofida, Siti; Muchlisin, M Artabah (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2479, 2023)
Anxiety disorder is a psychological disorder associated with the existence of mental disorders and experiencing constant anxiety. In C. odorata , part of the flower has the potential as a sedative for the nervous system and for dealing with anxiety. The study aims to analyze the potential compound content in Cananga odorata for treating anxiety disorders with In silico-based pharmacological network analysis. CO compound data from the KNApSAck database, Absorption, Distribution, Metabolism, and Excretion (ADME) screening using SwissADME, predicted target proteins using Swiss Target Prediction, GeneCards, Venny, String DB pharmacological network analysis, Visualization with Cytoscape version 3.10.0, and Way2drug. The results of the pharmacological tissue analysis of the compound content in C. odorata obtained 45 compounds, and 18 known active components meet the criteria of Absorption, Distribution, Metabolism, and Excretion (ADME) that correspond to the drug compounder (Drug Likeness/DL). Based on the pathway that correlates with anxiety disorder therapy are the neurotransmitter systems like serotonin receptors and dopamine receptors. The known therapeutic target proteins are HTR1A, HTR2A, SLC6A4, NR3C1, MAOA, DRD4, HSP90AA1, JUN, ten active compounds associated with C. odorata namely Anonaine, (+)-Reticuline, linalool, (-)-Coreximine, Micheline A, (-)-Ushinsunine beta-N-oxide, 4-Terpineol, alpha-Terpeneol, Sampangine, Anaxagoreine. Based on the results of research, C. odorata is potentially a treatment for anxiety disorder.